2015
DOI: 10.1523/jneurosci.0387-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminally Truncated Forms of Tau, But Not Full-Length Tau or Its C-Terminal Fragments, Are Released from Neurons Independently of Cell Death

Abstract: Recent evidence suggests that tau aggregation may spread via extracellular release and subsequent uptake by synaptically connected neurons, but little is known about the processes by which tau is released or the molecular forms of extracellular tau. To gain insight into the nature of extracellular tau, we used highly sensitive ELISAs, which, when used in tandem, are capable of differentiating between full-length (FL) tau, mid-region-bearing fragments, and C-terminal (CT) fragments. We applied these assays to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 55 publications
12
147
1
Order By: Relevance
“…It is worth noting that hypophosphorylated intact Tau was detected in conditioned medium of neuronal cultures in a previous study [11], although such extracellular Tau was demonstrated to be non-exosome associated, as Tau is barely detected in exosomal preparations, probably due to the limited material loaded. By contrast, another report stated that only C-terminally truncated Tau lacking the microtubule binding domain is released by cultured neurons or other types of cells [50] and a small fraction of extracellular Tau (<0.2%) is indeed present in exosomes. The cause of the discrepancy (truncated Tau v.s.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that hypophosphorylated intact Tau was detected in conditioned medium of neuronal cultures in a previous study [11], although such extracellular Tau was demonstrated to be non-exosome associated, as Tau is barely detected in exosomal preparations, probably due to the limited material loaded. By contrast, another report stated that only C-terminally truncated Tau lacking the microtubule binding domain is released by cultured neurons or other types of cells [50] and a small fraction of extracellular Tau (<0.2%) is indeed present in exosomes. The cause of the discrepancy (truncated Tau v.s.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the N-terminal fragments of tau [13] or the "C-terminally truncated forms of Tau" [69] are secreted into the extracellular space. This extracellular tau is regulated by neuronal activity [99] and could modulate Aβ secretion [13]-although data are contradictory [69].…”
Section: In Vitromentioning
confidence: 99%
“…This extracellular tau is regulated by neuronal activity [99] and could modulate Aβ secretion [13]-although data are contradictory [69].…”
Section: In Vitromentioning
confidence: 99%
“…, 2015) and may produce neurotoxic fragments (Park and Ferreira, 2005; Lang et al. , 2014), generate products that show increased release from neurons (Kanmert et al. , 2015), or produce fragments with a modified MT interaction (Derisbourg et al.…”
Section: Introductionmentioning
confidence: 99%